FAKTOR RISIKO KETIDAKPATUHAN PENGOBATAN PENDERITA TUBERKULOSIS PARU DI KOTA KENDARI - Asriati Asriati; La Ode Alifariki (Poltekkes Kemenkes Malang, 2019)
The aim of this study was to analysis the risk factors incompliance treatment of TB patient.in Kendari city. The study was a control case design, with 136 respondents consist of 68 cases and 68 controls .The cases samples were all newly TB patients aged 15 years old and above who incompliance treatment .The control samples were all newly TB patients aged 15 years old and above, who compliance treatment. The analysis of the data with tabulation system and statistics by the SPSS with odds ratio. The results of the study indicated that from three variables assumed risky to incompliance to take medicine, there were four variables found to have risk of incompliance , i.e., knowledge OR is 5,492, and activity supervisor to take medicine OR is 4,166. The conclusion : Knowledge, activity supervisor to take medicine, side effect of the drug and feeling better were constitute risk factors to incompliance treatment of TB patient in kendari city